Pluskwiaki z nadrodziny Pentatomoidea Reut. (Hemiptera, Heteroptera) Wyżyny Śląskiej - Lis, Jerzy A. (1960– ); Państwowe Wydawnictwo Naukowe (1951–1992); Polska Akademia Nauk. Instytut Zoologii (Państwowe Wydawnictwo Naukowe, 1987)
Bibliogr. p. 370-371
P. 359-372 ; 24 cm
Abstract in English, Russian. Taxa in Latin.
Keywords: Pentatomoidea; plant communities; new species to a regional fauna; hosts; geographical distribution; Poland; rare species; Silesian Upland; insects; Insecta; heteropterans; Heteroptera; hemipterans; Hemiptera

Lądowe pluskwiaki różnoskrzydłe (Heteroptera) Roztocza - Cmoluchowa, Alicja; Lechowski, Lech; Polska Akademia Nauk. Muzeum i Instytut Zoologii (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 1994)
W serii gł.: Fragmenta Faunistica, t. 37, nr 7
Bibliogr. s. 198-199
S. 181-199 ; 25 cm
Streszcz. ang. Nazwy taksonów również łac.
Keywords: Roztocze (region); hemipterans; Hemiptera; heteropterans; Heteroptera; Roztochia (region); Poland; Roztocze National Park; zoocenosis; insects; Insecta; new species to the Polish fauna

Piewiki (Homoptera, Auchenorrhyncha) Pienin - Nast, Janusz (1908–1991) (Państwowe Wydawnicwto Naukowe, 1976)
p. 145-183
bibliogr. p. 37-38
39 p. : ill. ; 24 cm
Abstract in Russian, English
Keywords: planthoppers and leafhoppers; Auchenorrhyncha; Cicadinea; hemipterans; Hemiptera; insects; Insecta; Pieniny (mountains); Poland; geographical distribution

Tytthus pygmaeus (Zett.) - nowy gatunek dla fauny Polski oraz niektóre gatunki pluskwiaków (Hemiptera - Heteroptera) nowe dla fauny regionu warmińsko-mazurskiego = Tytthus pygmaeus (Zett.) - novyj vid dlâ fauny Pol'ši i nekotorye drugie vidy polužestkokrylyh (Hemiptera - Heteroptera) novye dlâ fauny Varminsko-Mazurskogo priozer'â - Mikołajski, Melchior (Państwowe Wydawnictwo Naukowe, 1962)
p. 251-[256]
bibliogr. p. 4-5 (254-255)
5, [1] p. ; 25 cm
Abstract in Russian, English. Taxa in Latin
Keywords: Tytthus pygmaeus -- Polska -- wykazy faunistyczne [KABA]; Pluskwiaki różnoskrzydłe -- Polska -- wykazy faunistyczne [KABA]; Tytthus pygmaneus; insects; Insecta; hemipterans; Hemiptera; heteropterans; Heteroptera; Poland

Pluskwiaki różnoskrzydłe (Heteroptera) rzeki Lubrzanki w Górach Świętokrzyskich - Krajewski, Stanisław; Państwowe Wydawnictwo Naukowe (1951–1992); Polska Akademia Nauk. Instytut Zoologii (Państwowe Wydawnictwo Naukowe, 1986)
W serii gł.: Fragmenta Faunistica, t. 30, nr 4
Bibliogr. p. 50
P. 45-51 ; 24 cm
Abstract in English, Russian. Taxa in Latin.
Keywords: hemipterans; Hemiptera; heteropterans; Heteroptera; geographical distribution; Insecta; insects; Poland; Świętokrzyskie Mountains; Holy Cross Mountains

Auchenorrhyncha (Homoptera) Wyżyny Lubelskiej i Roztocza. Cz. 1 Fulgoroidea - Nast, Janusz (1908–1991) (Państwowe Wydawnictwo Naukowe, 1979)
Bibliogr. p. 13
13 p. ; 25 cm
Abstract in Russian, English. Taxa in Latin
Keywords: hemipterans; Insecta; insects; Poland; planthoppers and leafhoppers; Hemiptera; Auchenorrhyncha; Cicadinea; Lublin Upland

Przyczynek do znajomości koliszków (Homoptera, Psyllodea) Lubelszczyzny = Materialy k poznaniû listoblošek (Homoptera, Psyllodea) Lûblinskoj vozvyšennosti - Klimaszewski, Sędzimir Maciej (1937–2001) (Państwowe Wydawnictwo Naukowe, 1968)
p. 9-20
Bibliogr. p. 11
12 p. ; 25 cm
Abstract in Russian, German
Keywords: Psyllodea; Psylloidea; psyllids; jumping plantlice; hemipterans; Hemiptera; Insecta; insects; Poland; species biology; morphology; geographical distribution; Lublin Upland

Czerwce = Coccoidea - Kawecki, Zbigniew (1908–1981) (Państwowe Wydawnictwo Naukowe, 1985)
Na s. tyt. nr 39 "Katalogu fauny Polski."
Bibliogr. pp. 84-98. Index
106, [2] p., [1] leaf of plates ; 25 cm
Taxa in Latin.
Keywords: classification; Poland; geographical distribution; catalogue; insects; Insecta; hemipterans; Hemiptera; scale insects; Coccoidea

Przegląd wioślaków (Corixidae) krajowych - Jaczewski, Tadeusz (1899–1974) (nakł. Polskiego Państwowego Muzeum Przyrodniczego, 1924)
W serii gł.: Prace Zoologiczne Polskiego Państwowego Muzeum Przyrodniczego = Annales Zoologici Musei Polonici Historiae Naturalis ; t. 3, z. 1-2
W nagł. odmienna nazwa i numeracja serii: Annales Zoologici Musei Polonici Historiae Naturalis - Vol. 3, Nr 1-2. 1 X 1924
Tyt. nagł
Bibliogr. p. 94-96
98 p., 3 leaves of plates : ill. ; 24 cm
Keywords: rhynchota; siphonata; Insecta; insects; Hemiptera; bugs, true; pluskwiaki; Corixidae; Heteroptera; true bugs; plant bugs; Poland; review of the species; morphological features

Sigara glossata (Lundbl.) w Polsce. (Heteroptera, Corixidae) = Sigara glossata (Lundbl.) in Polen. (Heteroptera, Corixidae) - Jaczewski, Tadeusz (1899–1974) (nakł. Państwowego Muzeum Zoologicznego, 1932)
Liczbowanie stron również: S. 462-464
Z jednym rys. w tekście
3 s. : ill. ; 25 cm
Abstract in German. Taxa in Latin
Keywords: Radom; Poland; Insecta; insects; hemipterans; Hemiptera; Corixidae; Sigara glossata

Kilka nowych lub mniej znanych w faunie Polskiej gatunków pluskwiaków (Heteroptera) = Einige für Polen neue oder wenig bekannte Heteroptern - Arten - Jaczewski, Tadeusz (1899–1974) (nakł. Państwowego Muzeum Zoologicznego, 1932)
Liczbowanie stron również: S. 417-418
2 p. : ill. ; 25 cm
Abstract in German. Taxa in Latin
Keywords: Ukraine; Belarus; Poland; Insecta; insects; hemipterans; Hemiptera; Heteroptera

Kilka nowych lub mniej znanych w faunie polskiej gatunków pluskwiaków (Heteroptera). 2 = Einige für Polen neue oder wenig bekannte Heteteropteren-Arten. 2 - Jaczewski, Tadeusz (1899–1974) (nakł. Państwowego Muzeum Zoologicznego, 1933)
Tyt. nagł.
Oznaczenie stron również: S. 9-12
4 p. ; 24 cm
abstract in German. Taxa in Latin.
Keywords: Podolia; Ukraine; Poland; true bugs; Insecta; insects; hemipterans; Hemiptera; Heteroptera

Studies on the genus Lecanium BURM. 2, The Yew Scale, Lecanium pomeranicum sp. n. and some related species (Homoptera, Coccoidea, Lecaniidae) : [Pl. I, 1 table and 3 text-figures] - Kawecki, Zbigniew (1908–1981) (Państwowe Wydawnictwo Naukowe, 1954)
Liczbowanie stron również: S. [9]-22
Bibliogr. p. 19-20
14 p., 1 leaf of plates : ill. ; 24 cm
Abstract in Polish, Russian. Taxa in Latin
Keywords: North America; Poland; Europe; Polonia; new taxa; host plants; parasites; yews; Taxus; Insecta; insects; hemipterans; Hemiptera; tortoise scales; wax scales; soft scale; Coccidae; Fletcher scale; Parthenolecanium fletcheri; Lecanium pomeranicum; yew scale; Parthenolecanium pomeranicum

Materiały do fauny pluskwiaków (Hemiptera) Polski = Materialy k faune polyžestkokrylyh (Hemiptera) Pol'₍i - Smreczyński, Stanisław (1872–1954) (Państwowe Wydawnictwo Naukowe, 1954)
146 p. ; 25 cm
Abstract in Russian, French. Taxa in Latin
Keywords: Hemiptera; hemipterans; insects; Insecta; Poland; new species to the Polish fauna; geographical distribution

Interesujące i rzadkie gatunki Hemiptera-Heteroptera charakterystyczne dla torfowisk z okolic Sosnowicy (pow. Parczew, woj. lubelskie) = Bolee interesnye i redkie vidy Hemiptera-Heteroptera, harakternye dlâ torfânyh bolot okrestnostej Sosnovicy (r-n Parčev, Lûblinskoe voevodstvo) - Strawiński, Konstanty (1892–1966) (Państwowe Wydawnictwo Naukowe, 1965)
Liczbowanie stron również: P. 399-402
Bibliogr. p. 3-4 (401-402)
4 p. ; 25 cm
Abstract in German, Russian. Taxa in Latin
Keywords: tyrfobionts; Sosnowica; geographical distribution; Poland; peatlands; heteropterans; Heteroptera; Parczew (region); insects; Insecta; hemipterans; Hemiptera

Morfologia postaci dojrzałych Plataspidae i wybranych rodzin Pentatomoidea (Hemiptera, Heteroptera) - Ślipińska Ewa (Muzeum i Instytut Zoologii PAN, 2000)
Przewód doktorski przeprowadzony w Muzeum i Instytut Zoologii PAN
Praca wykonana w Katedrze Biosystematyki UO
Praca doktorska. Muzeum i Instytut Zoologii PAN, 2000
Bibliogr. p. 75-84
97 [52] p. : ill. ; 30 cm
Keywords: Plataspidae; imago; morphology; Plataspididae; insects; Insecta; adults; hemipterans; Hemiptera

Three new aphid species (Homoptera, Aphididae) from Mongolia - Holman, Jaroslav; Szelęgiewicz, Henryk (1927–1983) (Państwowe Wydawnictwo Naukowe, 1975)
Liczbowanie stron również: S. 431-440
With 16 text-figures
Bibliogr. p. 10 (440)
10 p. : ill. ; 24 cm
Abstract in Polish, Russian. Taxa in Latin
Keywords: Acyrthosiphon crepidis; Brachycaudus plantaginis; Smiela mongolica; host plants; new taxa; Mongolia; true bugs; bugs, true; hemipterans; insects; Aphididae; Hemiptera; Insecta

Nowe stanowiska Aphelocheirus aestivalis (Fabr.) w Polsce. (Heteroptera, Naucoridae) = Neue Fundorte von Aphelocheirus aestivalis (Fabr.) in Polen. (Heteroptera, Naucoridae) - Jaczewski, Tadeusz (1899–1974) (nakł. Państwowego Muzeum Zoologicznego, 1932)
Liczbowanie stron również: S. 413-416
4 p. ; 25 cm
Abstract in German. Taxa in Latin
Keywords: Ukraine; Poland; Belarus; Insecta; insects; hemipterans; Hemiptera; saucer bug; Aphelocheirus aestivalis

Rewizja systematyczna , filogeneza i klasyfikacja, pluskwiaków z grupy rodzajowej Privesa (Hemiptera: Fulgoromorpha: Ricanidae - Stroiński, Adam. (Muzeum i Instytut Zoologii PAN, 2007)
Praca doktorska. Muzeum i Instytut Zoologii PAN, 2007
Bibliogr. p. 169-176
269 p. : col. ill. ; 30 cm
Keywords: Insecta; planthoppers; hemipterans; insects; phylogenetics; fulgoromorpha; Hemiptera; Ricaniidae; classification; taxonomy

Hemiptera-Heteroptera mniej znane lub nowe dla fauny Bułgarii = Hemiptera-Heteroptera menee izvestnye ili novye dlâ fauny Bolgarii - Strawiński, Konstanty (1892–1966) (Państwowe Wydawnictwo Naukowe, 1959)
Liczbowanie stron również: S. 235-[246]
Bibliogr. p. 10-11 (244-245)
11, [1] p. ; 25 cm
Abstract in Polish, Russian. Taxa in Latin
Keywords: geographical distribution; new species to the Bulgarian fauna; Republic of Bulgaria; Bulgaria; insects; Insecta; hemipterans; Hemiptera; heteropterans; Heteroptera

Heteroptera aus Korea. T. 2, (Aradidae, Berytidae, Lygaeidae, Pyrrhocoridae, Rhopalidae, Alydidae, Coreidae, Urostylidae, Acanthosomatidae, Scutelleridae, Pentatomidae, Cydnidae, Plataspidae) - Josifov, Mihail Vladimirov; Keržner, Izjaslav Moiseevič; Państwowe Wydawnictwo Naukowe (1951–1992); Polska Akademia Nauk. Instytut Zoologii (Państwowe Wydawnictwo Naukowe, 1978)
Liczbowanie stron również: S. 137-196
Bibliogr. p. 58-59 (194-195)
60 p. : ill. ; 25 cm
Abstract in English, Polish. Taxa in Latin
Keywords: Heteroptera; Hemiptera; hemipterans; Insecta; insects; new taxa; classfication; identification key; North Korea

Calluneyrodes callunae (Ossiannilsson, 1947) (Hemiptera: Aleyrodidae) - a whitefly new to the fauna of Poland with updated check list of Polish Aleyrodidae - Klasa, Anna; Palaczyk, Andrzej (Museum and Institute of Zoology, PAS, 2011)
Calluneyrodes callunae (Ossiannilsson, 1947) has been collected in Nowy Targ Dale on the heather moorland Baligówka near Czarny Dunajec. It is the first record of this little-known European species in Poland. A list to each Polish species record of Aleyrodidae is presented.
Bibliogr.: p. 14-15
P. 11-15 : ill. color. ; 25 cm
Abstracts in Polish. Taxa in Latin
Keywords: Insecta; insects; Hemiptera; hemipterans; Aleyrodidae; whiteflies; Calluneyrodes callunae; Poland; Baligówka; new record; Calluna vulgaris; common heather; linga; heather; parasites; geographical distribution

Wioślaki (Corixidae, Heteroptera) z Mongolskiej Republiki Ludowej i niektórych obszarów przyległych = Corixidae (Heteroptera) iz Mongol'skoj Narodnoj Respubliki i nekotoryh sopredel'nyh oblastej - Jaczewski, Tadeusz (1899–1974) (Państwowe Wydawnictwo Naukowe, 1960)
Liczbowanie stron również: S. 305-314
Bibliogr. p. 7-8 (311-312)
10 p. : ill. : 25 cm
Abstract in Polish, Russian. Taxa in Latin
Keywords: Holarctic; geographical distribution; Mongolia; insects; Insecta; hemipterans; Hemiptera; heteropterans; Heteroptera; Corixidae

Nowe dla Polski lub mniej znane gaunki Homoptera. 3. = Novye dlâ Pol'ši ili menee izvestnye vidy Homoptera. 3 - Nast, Janusz (1908–1991) (Państwowe Wydawnictwo Naukowe, 1955)
P. 213-232
Bibliogr. p. 17-18 (229-230)
20 p. : ill. ; 25 cm
Abstract in Russian, English. Taxa in Latin
Keywords: Auchenorrhyncha; Cicadinea; planthoppers and leafhoppers; Hemiptera; hemipterans; Insecta; insects; Poland; new species to the Polish fauna; geographical distribution; natural history; collections; Zoological Institute PAS

Pluskwiaki różnoskrzydłe wodne (Hemiptera-Heteroptera aquatilia) okolic Poznania = Die Wasserwanzen (Hemiptera-Heteroptera aquatilia) der Umgegend von Poznań - Wróblewski, Aleksander (1911–1985) (nakł. Państwowego Muzeum Zoologicznego ;, 1939)
Liczbowanie stron również: S. 107-142
Z 2 tabelami i mapą na tabl. IV.
Bibliogr. p. 33 (139)
36 p., 2 folded leaf of plates : ill. ; 25 cm
Abstract in German. Taxa in Latin
Keywords: Poznań (region); Poland; zoocenology; true water bugs; Nepomorpha; insects; Insecta; hemipterans; Hemiptera; Heteroptera